Criminology and the Anthropocene. (July 2015) - Shearing, Clifford
The article explores how criminology is responding to, and might respond to, the challenges presented by changes in earth systems, and the reasons for them, that the term 'Anthropocene' signals. It begins with a very brief review of these developments and the meaning of the term. It then examines the responses within criminology that have emerged under the sign 'green criminology'. Thereafter it explores how criminology might respond to the challenges of the Anthropocene by using a 'security governance' lens.